Irama Tragika dalam Naskah Raja Lear karya William Shakespeare - Handayani, Lusi; Irianto, Ikhsan Satria; Gustyawan, Tofan (Creativity And Research Theatre Journal, 2023)
This tragic rhythm research aims to explore the strategic tragedy and the characteristic Shakespearean Tragedy in William Shakespeare's King Lear. The material object in this study is the King Lear by William Shakespeare translated by Trisno Sumardjo, while the formal object used is Fergusson's Tragic Rhythm theory. The research method used is a qualitative method with data collection techniques, text studies and literature studies. The results achieved in this study are the characteristics of Shakespearean Tragedy in King Lear's consisting of the fall of the king, the omnipotence of destiny and characters who have tragic defects. Meanwhile, the tragic rhythm is found in three stages, the stage of King Lear's obsession, the stage where King Lear encounters obstacles and the stage when King Lear realizes his mistake.AbstrakPenelitian irama tragika ini bertujuan untuk menelusuri strategi tragedi dan karakteristik shakespearean tragedy dalam naskah Raja Lear karya William Shakespeare. Objek material dalam penelitian ini adalah naskah Raja Lear karya William Shakespeare terjemahan Trisno Sumardjo, sedangkan objek formal yang digunakan adalah teori Irama Tragika Fergusson. Metode penelitian yang digunakan adalah metode kualitatif dengan teknik pengumpulan data, yaitu studi teks dan studi pustaka. Hasil yang dicapai dalam penelitian ini adalah karakteristik Shakespearean Tragedy dalam naskah Raja Lear terdiri dari kejatuhan raja, kemahakuasaan takdir dan tokoh yang memiliki cacat tragis. Sedangkan irama tragika ditemukan dalam tiga tahapan, yaitu tahap obsesi Raja Lear, tahap Raja Lear mendapatkan hambatan dan tahap Raja Lear menyadari kesalahannya.